2005
DOI: 10.1162/089892905774597263
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Encoding of Polyphonic Melodies in Musicians and Nonmusicians

Abstract: Abstract& In music, multiple musical objects often overlap in time. Western polyphonic music contains multiple simultaneous melodic lines (referred to as ''voices'') of equal importance. Previous electrophysiological studies have shown that pitch changes in a single melody are automatically encoded in memory traces, as indexed by mismatch negativity (MMN) and its magnetic counterpart (MMNm), and that this encoding process is enhanced by musical experience. In the present study, we examined whether two simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
128
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(143 citation statements)
references
References 83 publications
14
128
0
1
Order By: Relevance
“…Musicians have also been found to have more enhanced MMNm than nonmusicians. This has been attributed to cortical reorganization resulting from long-term training because the source of MMN is located mainly in the auditory cortex (Fujioka et al, 2005). Our study is the first to show that this upper tone dominance at the cortical level extends to the subcortical sensory system.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Musicians have also been found to have more enhanced MMNm than nonmusicians. This has been attributed to cortical reorganization resulting from long-term training because the source of MMN is located mainly in the auditory cortex (Fujioka et al, 2005). Our study is the first to show that this upper tone dominance at the cortical level extends to the subcortical sensory system.…”
Section: Discussionsupporting
confidence: 51%
“…For example, behavioral studies have shown that changes occurring in the upper voice are more easily detected than those in the middle or lower voice (Palmer and Holleran, 1994;Crawley et al, 2002). Furthermore, electrophysiological studies showed larger and earlier mismatch negativity magnetic field (MMNm) responses for deviations in the upper voice melody than in the lower voice (Fujioka et al, 2005(Fujioka et al, , 2008. Musicians have also been found to have more enhanced MMNm than nonmusicians.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we might see not also differences in asymmetry across groups for WM, but also within groups across different conditions, i.e., due to different levels of complexity in the music. For instance, although musicians tend to rely on left-sided brain for music processing in a greater extent than non-musicians (Fujioka, Trainor, Ross, Kakigi, & Pantev, 2005), possibly explained by a more consciously learned or analytic approach to the musical input, complex music has been reported to drive even trained musicians into strongly using their 'right brain' (Vollmer-Haase, Finke, Hartje, & Bulla-Hellwig, 1998;McGilchrist, 2010).…”
Section: Conclusion and Further Researchmentioning
confidence: 99%
“…A series of recent studies has suggested that these and other basic properties of the auditory system, which are shared by a wide variety of species, may help account for some fundamental aspects of Western music, including the dominance of high-register instruments (i.e., instruments with high fundamental frequencies) in carrying the melody (3)(4)(5)(6)(7), as well as the dominance of low-register instruments (such as bass or bass drum) in defining the meter or rhythm (8). In the latter case, a study by Hove et al (8) involving both behavioral and EEG experiments reported that time encoding was superior for low-vs. high-pitched sounds and suggested that this superior time encoding could explain why low instruments generally lay the rhythm in music.…”
mentioning
confidence: 99%